A Practical Case Study of Panel Evaluations for Vehicle Design Development - KOYAMA, Noboru; YOSHIDA, Satoshi; YAMASHITA, Mikio (INTERNATIONAL JOURNAL OF AFFECTIVE ENGINEERING, 2013)
In prior research (Reference 1), I surveyed and compared several aspects of the panel evaluation system in today's Japanese, American and European automotive industries, including the operation of the system, the methodology, and the actions taken by companies based on the evaluation results, establishing patterns and clarifying points of difference. In doing so, I uncovered some major companies that had effectively applied panel evaluation systems in their design department which appointed in-house panelists (persons who evaluate designs during their development) and carried out their decision-making with few errors. Based on these findings, I received the cooperation of a Japanese automaker (X Corporation) to participate in the workings of an improved panel evaluation system in actual automotive design development. Specific improvement measures included modifications to the panelist selection methodology and training of panelists to think ahead more effectively than average users, as well as a new verification system and new evaluation criteria to guide panelists in making more reliable evaluations. This led to improved reliability of evaluation results and full application of the results in the decision-making for the actual design. This paper summarizes the process in the form of a case study.